Penerapan Model Discovery Learning dengan berbantuan Media Pop Up Book dalam Meningkatkan Hasil Belajar Peserta Didik Kelas VI SD 2 Singocandi - Arlinda Risti Aryanti; Siti Masfuah, Tianida Nilamsari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of implementing the Discovery Learning model supported by Pop Up Book media in improving the learning outcomes of sixth-grade students. The method used is classroom action research (CAR) conducted in two cycles. The research subjects consisted of 34 sixth-grade students at SD 2 Singocandi. Data were collected through written tests, observations, and documentation during the learning process. The results showed that the implementation of the Discovery Learning model with Pop Up Book media successfully improved student learning outcomes, with the mastery percentage increasing from 44% in the pre-cycle to 59% in cycle I, and further rising to 79% in cycle II. Thus, it can be concluded that using the Discovery Learning model together with Pop Up Book media is effective in enhancing the learning outcomes of sixth-grade students. Therefore, it is recommended that teachers consider using innovative learning models and media that support the learning process to improve student achievement and motivation.